Pemahaman Siswa Kelas XI SMA Unggulan Kota Padang Terhadap Konsep Reaksi Pengendapan pada Pembelajaran Materi Kelarutan dan Hasilkali Kelarutan - Monica Prima Sari; Hernani Hernani; Sri Mulyani (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2019)
This paper describes 11th grade students’ understanding of the concept of precipitation reaction at the end of the learning process of solubility and solubility product. Precipitation reaction is an important reaction in industry, pharmacy, and daily life. In the learning process, students are asked to predict the formation of precipitation based on their understanding of solubility and solubility product concepts. Thirty eleventh grade students in one of the best senior high schools in Padang were chosen as the subject of this study. Classroom learning process was observed and recorded. Data of students’ understanding were collected through a set of essay problems which was validated through expert judgment, and then integrated in students’ end-of-chapter test. Through qualitative analysis, this study revealed some mistakes and misconceptions that students have regarding the application of precipitation reaction concept, and possible sources of them. Recommendations for improving the quality of learning this concept in the future are provided at the end of the paper